Milk Polar Lipids in a High‐Fat Diet Can Prevent Body Weight Gain: Modulated Abundance of Gut Bacteria in Relation with Fecal Loss of Specific Fatty Acids. Issue 4 (25th January 2019) - Milard, Marine; Laugerette, Fabienne; Durand, Annie; Buisson, Charline; Meugnier, Emmanuelle; Loizon, Emmanuelle; Louche‐Pelissier, Corinne; Sauvinet, Valérie; Garnier, Lorna; Viel, Sébastien; Bertrand, Karène; Joffre, Florent; et al.
Abstract : Scope: Enhanced adiposity and metabolic inflammation are major features of obesity associated with altered gut microbiota and intestinal barrier. How these metabolic outcomes can be impacted by milk polar lipids (MPL), naturally containing 25% of sphingomyelin, is investigated in mice fed a mixed high‐fat (HF) diet . Methods and results: Male C57Bl/6 mice receive a HF‐diet devoid of MPL (21% fat, mainly palm oil, in chow), or supplemented with 1.1% or 1.6% of MPL (HF‐MPL1; HF‐MPL2) via a total‐lipid extract from butterserum concentrate for 8 weeks. HF‐MPL2 mice gain less weight versus HF ( p  < 0.01). Diets do not impact plasma markers of inflammation but in the liver, HF‐MPL2 tends to decrease hepatic gene expression of macrophage marker F4/80 versus HF‐MPL1 ( p = 0.06). Colonic crypt depth is the maximum in HF‐MPL2 ( p  < 0.05). In cecal microbiota, HF‐MPL1 increases Bifidobacterium animalis versus HF ( p  < 0.05). HF‐MPL2 decreases Lactobacillus reuteri ( p  < 0.05), which correlates negatively with the fecal loss of milk sphingomyelin‐specific fatty acids ( p  < 0.05). Conclusion: In mice fed a mixed HF diet, MPL can limit HF‐induced body weight gain and modulate gut physiology and the abundance in microbiota of bacteria of metabolic interest. This supports further exploration of how residual unabsorbed lipids reaching the colon can impact HF‐induced metabolic disorders. Abstract : Milk polar lipids, a natural component of the milk fat globule membrane (MFGM), are an emerging functional ingredient. It has been shown in mice that when added to a high‐fat diet, 1.6% of milk polar lipids reduces body weight gain, modulates the abundance of bacteria of metabolic interest in the gut microbiota, and impacts colon morphology. The fecal excretion of fatty acids specific of sphingomyelin, typical of milk polar lipids, which remains partly unabsorbed by the intestine, can explain these effects.